Inflation Reports and Models : How Well Do Central Banks Really Write? - Bulir, Ales (IMF Working Papers; Working Paper ;, 2014)
We offer a novel methodology for assessing the quality of inflation reports. In contrast to the existing literature, which mostly evaluates the formal quality of these reports, we evaluate their economic content by comparing inflation factors reported by the central banks with ex-post model-identified factors. Regarding the former, we use verbal analysis and coding of inflation reports to describe inflation factors communicated by central banks in real time. Regarding the latter, we use reduced-form, new Keynesian models and revised data to approximate the true inflation factors. Positive correlations indicate that the reported inflation factors were similar to the true, model-identified ones and hence mark high-quality inflation reports. Although central bank reports on average identify inflation factors correctly, the degree of forward-looking reporting varies across factors, time, and countries.